The Future of Irish‐UK Relations: Borders and Identities after Brexit: Introduction. Issue 1 (7th October 2022) - Colfer, Barry; Diamond, Patrick
Abstract: It is apparent that the consociational framework established by the Belfast/Good Friday Agreement (B/GFA) is under threat, while the UK's withdrawal from the EU poses major challenges for maintaining peace, prosperity and social cohesion in Northern Ireland (NI). The contributions to this special collection examine key elements of the post‐Brexit reality, with a particular focus on NI and the future of the intergovernmental bodies established by the B/GFA. The implications of the UK government's attempt unilaterally to disapply parts of the Protocol on Ireland/Northern Ireland are examined.